Enhancing the Spectroscopic Properties of Rhodamine B Via the Nano-Concentration Effect - Naif, Hanan Auda; Al-Obaidi, Ruba; M. Abdulmunem, Oday (Malaysian Journal of Science, 2025)
Developing nano-liquid materials with ultra-low concentrations leads to new or improved methods, as well as resolving issues in previous studies. Nano-liquid materials require special treatment because they are very sensitive materials. Many techniques have been developed, including the optical cavity technique, which depends on increasing the path length of the light beam between two dielectric mirrors to obtain more accurate and sensitive measurements. This method also provides beneficial information about the chemical composition. In this study, broadband cavity-enhanced absorption spectroscopy was used at a range of visible wavelengths to obtain spectra of rhodamine B (C28H31ClN2O3) at room temperature. The liquid phase of rhodamine B was chosen because it is the most complicated and volatile phase. The spectral analyses showed the fine structure of the aqueous solution of rhodamine B and the different molecular dynamics. The processes of the electron dynamics inside the molecules also changed at the ultra-low sample concentrations achieved working at the nanomolar scale. Combining experimental and data analysis via simulation programs has many benefits, such as reducing the time needed to study the materials, as it presents a typical design with fewer issues. In addition, costly, scarce, or difficult-to-store materials should be studied at low concentrations, and these combined studies can yield results without using these materials. The novelty of our research is the successful study of low concentrations of liquid samples. The high quality of the data, demonstrated by the goodness-of-fit parameters, allows for further analyses. Spectral analysis of nano-concentrations of rhodamine B shows new multiphoton absorption processes that drive the shifts in peak intensity. The solvent interaction effects caused changes in the binding energy states of the molecular structure of the sample. Here, we present a new spectral analysis of rhodamine B in aqueous solution using the broadband cavity-enhanced absorption spectroscopy (BBCEAS) technique.